Personalisation for all: making adaptive course composition easy - CONLAN, OWEN; DAGGER, DECLAN; WADE, VINCENT PATRICK (IEEE, 2005)
The goal of personalised eLearning is to support e-learning content, activities and collaboration, adapted to the specific needs and influenced by specific preferences of the learner and built on sound pedagogic strategies. One of the major challenges to the mainstream adoption of personalised eLearning is the complexity and time involved in composing the adaptive learning experience. The key goal in personalized eLearning development tools is to sup-port the teacher in composing adaptive and non-adaptive eLearning experiences. One of the arguments of this paper is that these learning experiences should be activityoriented and pedagogically driven. Presented is a detailed discussion of the challenges of composing adaptive courses and in particular the difficulties and possible techniques in composing appropriate models and information to support adaptive courses. The paper describes an adaptive course construction methodology which extends traditional eLearning syllabi development with design activities which support adaptivity definition, subject matter concept modelling, adaptivity technique selection as well as alternative instructional design template customisation. The paper then details the Adaptive Course Construction Toolkit (ACCT), which supports this methodology and illustrates the tools usage in the development of an adaptive course. Finally the paper presents an initial evaluation of the toolkit and its associated methodology.
PUBLISHED
Keywords: Adaptive course composition tools, Adaptive educational hypermedia systems, Personalised eLearning